Dysregulation of core neurodevelopmental pathways—a common feature of cancers with perineural invasion - González-Castrillón, Luz María; Wurmser, Maud; Öhlund, Daniel; Wilson, Sara Ivy (Frontiers in Genetics, 2023)
BACKGROUND: High nerve density in tumors and metastasis via nerves (perineural invasion - PNI), have been reported extensively in solid tumors throughout the body including pancreatic, head and neck, gastric, prostate, breast, colorectal cancers amongst others. Ablation of tumor nerves results in improved disease outcomes suggesting that blocking nerve-tumor communication could be a novel treatment strategy. However, the molecular mechanisms underlying this remain poorly understood. Thus, the aim here was to identify molecular pathways underlying nerve-tumor crosstalk and to determine common molecular features between PNI associated cancers. RESULTS: Analysis of head and neck (HNSCC), pancreatic and gastric (STAD) cancer Gene Expression Omnibus datasets were used to identify differentially expressed genes (DEGs). This revealed extracellular matrix components as highly dysregulated. To enrich for pathways associated with PNI, an analysis was performed on genes previously correlated with PNI in STAD and in 2 HNSCC studies where tumor samples were segregated by PNI status and found neurodevelopmental genes to be enriched. In datasets where tumor samples were not segregated by PNI, neurodevelopmental pathways accounted for 12-16% of the DEGs. Dysregulation of axon guidance genes was common to all cancers analyzed. By examining paralogue genes, a clear pattern emerged where at least one family member from several axon guidance pathway was affected in all cancers examined. Overall 17 different axon guidance gene families were disrupted including the Ephrin-Eph, Semaphorin-Neuropilin/plexin, Slit-Robo pathways. These findings were validated using The Cancer Genome Atlas and cross referenced to other cancers with a high incidence of PNI including colon, cholangiocarcinoma, prostate and breast cancers. Survival analysis revealed that expression levels of neurodevelopmental gene families impacted disease survival. CONCLUSIONS: These data highlight the importance of the tumor as a source of signals for neural tropism and neural plasticity as a common feature of cancer. The analysis supports the hypothesis that dysregulation of neurodevelopmental programs is a common feature associated with PNI. Further, the data suggested that different cancers may have evolved to employ alternative genetic strategies to disrupt the same pathways. Overall, these findings provide potential druggable targets for novel therapies of cancer management and provide multi-cancer molecular biomarkers.